Análise da eficácia da casca do cupuaçu (Theobroma grandiflorum) sobre o crescimento da Aeromonas hydrophila e Staphylococcus aureus - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
World demand for fish trade has been growing positively in recent decades. Due to this increase in demand it is necessary to intensify the production and in doing so the fish become more stressed and as a result become more susceptible to pathogen involvement, among which stand out the bacteria Staphylococcus aureus and Aeromonas hydrophila. Therefore, the use of plant extracts appears as the cupuaçuzeiro (Theobroma grandiflorum) bark has been studied for these purposes. Thus, the present work aimed to analyze the effect of in vitro extract of the cupuaçu bark (Theobroma grandiflorum) on the antimicrobial capacity of Aeromonas hydrophila and Staphylococcus aureus growth. The strains used were isolated from naturally infected fish from commercial fish farming. The strains of these bacteria were reactivated by overnight cultivation in TSB broth and then cultivated on TSA / Difco® tryptone agar medium for 18 hours and suspended in 0.9% NaCl saline to 0.5 MacFarland concentration. They were prepared and inoculated with the suspension of A. hydrophila and S. aureus with the aid of swab. After that, 6 mm paper discs were inoculated with 10 μl of the tested extracts and placed on the previously prepared plate, where discs without inoculation of extracts were also added. This was the negative control and the chloramphenicol antibiotic (30 μg) used as control positive. The test was done in 6 repetitions each. The plates were incubated at 37 ° C for 24 hours, where inhibition halos around the discs were subsequently evaluated. According to the obtained result, the cupuaçu bark extract was not able to inhibit the growth of the bacteria in any of the tested concentrations. The negative results may have been influenced by the extraction method and amount of concentration of the extract in question. Thus, it is necessary to continue the study of the T. grandiflorum bark using other extraction methods and in different quantities, considering that it has characteristics with great antimicrobial potential.
Keywords: Extratos vegetais; Halo; Patologias; CNPQ:: CIÊNCIAS AGRÁRIAS